Distribution of strain patterns in children with dilated cardiomyopathy. Issue 6 (7th May 2017) - den Boer, Susanna L.; du Marchie Sarvaas, Gideon J.; Klitsie, Liselotte M.; van Iperen, Gabriëlle G.; Tanke, Ronald B.; Helbing, Willem A.; Backx, Ad P.C.M.; Rammeloo, Lukas A.J.; Dalinghaus, Michiel; ten Harkel, Arend D.J.
Abstract : Objectives: This study aimed to evaluate the predicting value of quantitative and qualitative dyssynchrony parameters as assessed by two‐dimensional speckle tracking echocardiography (STE) on outcome in children with dilated cardiomyopathy (DCM). Furthermore, the reproducibility of these parameters was investigated. Background: In previous studies in adults with heart failure, several dyssynchrony parameters have been shown to be a valuable predictor of clinical outcome. Methods: This multicenter, prospective study included 75 children with DCM and 75 healthy age‐matched controls. Using STE, quantitative (time to global peak strain and parameters describing intraventricular time differences) and qualitative dyssynchrony parameters (pattern analysis) of the apical four‐chamber, three‐chamber, two‐chamber views, and the short axis of the left ventricle were assessed. Cox regression was used to identify risk factors for the primary endpoints of death or heart transplantation. Inter‐observer and intra‐observer variability were described. Results: During a median of 21 months follow‐up, 10 patients (13%) reached an endpoint. Although quantitative dyssynchrony measures were higher in patients as compared to controls, the inter‐observer and intra‐observer variability were high. Pattern analysis showed mainly reduced strain, instead of dyssynchronous patterns. Conclusions: In this study, quantitative dyssynchrony parameters were not reproducible, precluding their use in children. Qualitative pattern analysis showed predominantly reduced strain, suggesting that in children with DCM dyssynchrony may be a minor problem.